Rethinking the future : rethinking business, principles, competition, control and complexity, leadership, markets and the world (London ; Napierville, IL. : Nicholas Brealey, 1998)
This book presents about rethinking business, principles, competition, control & complexity, leadership, markets and the world.
Keywords: Management; Strategic planning; Organization; Competition; Competition; Organizational change; Organizational innovation; Strategic planning; Organizational effectiveness